مكونات الجملة البسيطة وترتيب عناصرها في اللغتين العربية والأتشية (دراسة تقابلية) (Jurnal Adabiya, 2022)
Dirasah Taqabuliyah (Contrastive Analysis Study) is a study of two different languages that aims at identifying the similarities and differences existing in the two languages. This contrastive analysis study often helps Arabic teachers provide faster understanding to their students by using a comparison of language rules between the target language and the students' mother tongue. In this research, the researcher managed to compare the two languages (Arabic and Aceh)  on the 1 sub-topics of the existing problems, namely Mukawwanat. Mukawwanat is the composition needed to form a simple sentence, furthermore, this study is a literature study in which data is obtained from various sources relevant to Arabic and Acehnese. Finally, this research resulted in several conclusions, among which is that Arabic and Acehnese languages have their respective features in the composition and elements of simple sentences that are distinct to one another.